2019
DOI: 10.1177/0306624x19842027
|View full text |Cite
|
Sign up to set email alerts
|

Thwarted Interpersonal Needs and Suicide Ideation Distress Among Psychiatric Inpatients: The Moderating Role of Criminal Associates

Abstract: Psychiatric inpatients are at elevated risk of suicide, and approximately half are criminal justice-involved. Their involvement with criminal associates may be linked to increased suicide ideation distress; however, this has not been examined. This study tested main effects of, and interactions between, thwarted belongingness (TB) or perceived burdensomeness (PB), time spent with associates, and associates’ criminal involvement predicting suicide ideation distress. In our study, psychiatric inpatients ( n = 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
(62 reference statements)
2
4
0
Order By: Relevance
“…Additionally, even average levels of belonging buffer against the negative effects of stress related to CJ involvement. Our findings are congruent with previous findings that CJ‐involved individuals with a suicide attempt history are more likely to have relationship problems (Hakansson et al, 2010), and psychiatric inpatients who reported elevated TB and more time spent with criminals were most likely to also report “extreme” suicide ideation distress (Mitchell et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Additionally, even average levels of belonging buffer against the negative effects of stress related to CJ involvement. Our findings are congruent with previous findings that CJ‐involved individuals with a suicide attempt history are more likely to have relationship problems (Hakansson et al, 2010), and psychiatric inpatients who reported elevated TB and more time spent with criminals were most likely to also report “extreme” suicide ideation distress (Mitchell et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…This figure was created using the coefficients from mean-centered predictors, including the mean-centered AUDIT scores; however, the non-mean-centered AUDIT scores are presented on the x-axis against the negative effects of stress related to CJ involvement. Our findings are congruent with previous findings that CJ-involved individuals with a suicide attempt history are more likely to have relationship problems (Hakansson et al, 2010), and psychiatric inpatients who reported elevated TB and more time spent with criminals were most likely to also report "extreme" suicide ideation distress (Mitchell et al, 2019). Further, we found a significant interaction between alcohol-related severity and TB predicting a lifetime suicide attempt history; however, the nature of this interaction was contrary to our hypotheses.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations